Changes in drug use and HIV/AIDS risk-taking 1989-90 - Marsh, Alison; Loxley, Wendy; Hawks, D.; Quigley, A. (Taylor and Francis, 1995)
The Australian National AIDS and Injecting Drug Use Study was designed to monitor the riskbehaviour of Australian injecting drug users (IDUs) in a number of major cities, and to estimate the seroprevalence of those interviewed. Differences in risk behaviour found across 2 years in Perth are reported. One hundred and ninety-six Perth IDUs were interviewed in 1989, and 150 in 1990 using the same survey questionnaire, with a small cohort of 38 respondents being followed up across the 2 years.Significant injecting differences between 1989 and 1990 in both the cohort and independent samples were found. In general, these amounted to a greater likelihood that a new needle and syringe would be used on each injecting occasion, and a greater use of bleach in 1990 than in 1989. The most common response of respondents who said they had changed their drug use behaviour in 1990 was to report ceasing to share needles, while the most common response in 1989 was reduced sharing. There was an increased use of condoms for vaginal intercourse with all partners in both studies across the 2 years.Seropositivity for all new cases across the 2 years was 1.75%.It is apparent that there has been a significant shift in risky behaviour in the direction of greater safety across the 2 years. There is also objective corroborative evidence in increased demand for sterile injecting equipment sold through pharmacists, although there is no evidence that drug use increased significantly during the same period. It is concluded that the availability of sterile needles and syringes should be maintained and improved and that emphasis should be placed on encouraging safer sexualbehaviour among IDUs.